[Ulotka z logotypem Solidarności i czołgiem] . Flier with Solidarty logotype and a tank (Polska)
Red print on white paper. Flier contains a graphic image which represents a Solidarity logotype being crushed by a tank, with destroyed part reappearing under the tanks' caterpillars.